Globalization and the water-energy-food nexus – Using the global production networks approach to analyze society-environment relations. Issue 90 (December 2018) - Franz, Martin; Schlitz, Nicolas; Schumacher, Kim Philip
Highlights: Approach to unravel the complexities of the WEF Nexus in the context of globalization. Analysis of potential to combine Global Production Networks with WEF Nexus thinking. Utilization of the analytical category 'risk' for the analysis of the WEF Nexus. Abstract: The interrelation of the water-energy-food nexus and processes of globalization has to be understood thoroughly in order to address socio-economic inequalities and environmental change. However, unravelling the complexities of the water-energy-food nexus in the context of globalization poses conceptual and empirical difficulties. Economic globalization, e.g. through transnational trade and foreign direct investment, results in a global conjunction of actors, interests and impacts, strongly affecting patterns of resource extraction and environmental degradation, and local capabilities for its governance. In environmental economic geography, the global value chain and global production networks approaches have proved useful for the analysis of interrelations between governance structures, value, institutional contexts, and modes of resource consumption. In this paper, we discuss the potential of the global production networks approach to analyze society-environment relations in the context of the water-energy-food nexus and processes of globalization. To make our argument, we will use the case of manure and digestate, which results from meat and bioenergy production in the Oldenburger Münsterland, the center of livestock farming in Germany. The region is Germany's best developed agribusiness cluster, which is integrated into a transnational network of animal producers, feedstuff producers and meat processors. And it is also home to many biogas plants and several market leaders in bioenergy technology, strongly related to the livestock husbandry business. The case is an example of the three-way-mutual interactions among food, energy and water. The analysis will combine the perspective of the water-energy-food nexus with the analytical categories of the global production networks approach to provide a nuanced understanding of the socio-environmental implications of the global integration of a regional agri-food production cluster.